Odpowiedzi

2010-01-14T19:15:45+01:00
2(x-3)=4(1-y)
-(y-2)=3x

2x - 6 = 4-4y /:2
-y+2=3x

x-3=2-2y
-y+2=3x

x = -2y +5
-y + 2 = 3*(-2y + 5)

x = -2y +5
-y + 2 = -6y +15

x = -2y +5
-y+6y = 15 -2

x = -2y +5
5y = 13 /:5

x = -2y +5
y= 13/5

x = -2 * 13/5 + 5
y= 13/5

x= -26/5 + 5 = -5 1/5 +5 = -1/5
y= 13/5



1 5 1
2010-01-14T19:18:11+01:00
2x-6=4-4y
-y+2=3x
(przenosimy niewiadome na jedną stronę liczby na drugą)
2x+4y=4+6
-3x-y=-2/*4
(drugą linijkę mnożymy razy 4)
2x+4y=10
-12x-4y=-8
(skracamy 4y i -4y)
2x=10
-12x=-8
(sumujemy)
-10x=-2/:(-10)
x=1/5